2020
DOI: 10.1186/s12987-020-00192-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum-derived factors of breast cancer patients with brain metastases alter permeability of a human blood–brain barrier model

Abstract: Background: The most threatening metastases in breast cancer are brain metastases, which correlate with a very poor overall survival, but also a limited quality of life. A key event for the metastatic progression of breast cancer into the brain is the migration of cancer cells across the blood-brain barrier (BBB). Methods: We adapted and validated the CD34 + cells-derived human in vitro BBB model (brain-like endothelial cells, BLECs) to analyse the effects of patient serum on BBB properties. We collected serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…The tight junctions are highly developed and played a key role in the establishment of BBB [32,33]. Claudin 5 is the has been considered the important adhesion molecule of tight junctions involved in BBB in present study [34][35][36]. In our study, the results suggested that benzoinum could reduce the BBB injury by increasing in Claudin 5.…”
Section: Discussionsupporting
confidence: 48%
“…The tight junctions are highly developed and played a key role in the establishment of BBB [32,33]. Claudin 5 is the has been considered the important adhesion molecule of tight junctions involved in BBB in present study [34][35][36]. In our study, the results suggested that benzoinum could reduce the BBB injury by increasing in Claudin 5.…”
Section: Discussionsupporting
confidence: 48%
“…Wild type (WT) and PcdhgC3 knockout (KO) cerebEND cells were grown on gelatin-coated transwells (pore size 0.4 µm, Corning) for 6 days. The permeability assay was performed as previously described ( Curtaz et al, 2020 ) using 1 µM fluorescein (376 kDa, Sigma-Aldrich) for 1 h with aliquots taken from the basolateral compartment every 20 min. A parallel assay with cell-free transwells was used to calculate the endothelial permeability coefficient (Pe).…”
Section: Methodsmentioning
confidence: 99%
“…Although CXCL13-regulated cancer cell migration and metastasis has been reported in some cancers [ 16 ], the effect of CXCL13 in the motility of osteosarcoma cells remains uncertain. Numerous studies have shown that human physiological concentrations of CXCL13 are significantly increased in cancer patients compared with healthy controls [ 25 ]. Other cancer researchers have used treatment concentrations of CXCL13 in the range of 50–100 ng/mL [ 26 , 27 ], so the concentrations used in our study are physiologically relevant.…”
Section: Discussionmentioning
confidence: 99%